Iodine status in late pregnancy and psychosocial determinants of iodized salt use in rural northern Viet Nam - Jane Fisher; Thach Tran; Beverley Biggs; Tuan Tran; Terry Dwyer; Gerard Casey; Dang Hai Tho; Basil Hetze (The World Health Organization, 2011)
OBJECTIVE: To establish iodine status among pregnant women in rural northern Viet Nam and explore psychosocial predictors of the use of iodized salt in their households. METHODS: This prospective study included pregnant women registered in health stations in randomly-selected communes in Ha Nam province. At recruitment (< 20 weeks of gestation), sociodemographic factors, reproductive health, intimate partner relationship, family violence, symptoms of common mental disorders and use of micronutrient supplements were assessed. During a second assessment (> 28 weeks of gestation) a urine specimen was collected to measure urinary iodine concentration (UIC) and iodized salt use was assessed. Predictors were explored through univariable analyses and multivariable linear and logistic regression. FINDINGS: The 413 pregnant women who provided data for this study had a median UIC of 70 μg/l; nearly 83% had a UIC lower than the 150 μg/l recommended by the World Health Organization; only 73.6% reported using iodized salt in any form in their households. Iodized salt use was lower among nulliparous women (odds ratio, OR: 0.56; 95% confidence interval, CI: 0.32-0.96); less educated women (OR: 0.34; 95% CI: 0.16-0.71); factory workers or small-scale traders (OR: 0.52; 95% CI: 0.31-0.86), government workers (OR: 0.35; 95% CI: 0.13-0.89) and women with common mental disorders at recruitment (OR: 0.61; 95% CI: 0.38-0.98). CONCLUSION: The decline in the use of iodized salt in Viet Nam since the National Iodine Deficiency Disorders Control Programme was suspended in 2005 has placed pregnant women and their infants in rural areas at risk of iodine deficiency disorders.